2022
DOI: 10.3390/microorganisms10020424
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of BCG Vaccination and Plasma Amyloid: A Prospective, Pilot Study with Implications for Alzheimer’s Disease

Abstract: BCG vaccine has been used for 100 years to prevent tuberculosis. Not all countries, including the United States, adopted the initial World Health Organization recommendation to use BCG. Moreover, many Western countries that had routinely used BCG have discontinued its use. Recent population studies demonstrate lower prevalence of Alzheimer’s disease (AD) in countries with high BCG coverage. Intravesicular instillation of BCG is also used to treat bladder cancer that has not invaded the bladder muscle wall and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 46 publications
(53 reference statements)
1
6
0
Order By: Relevance
“…These studies mirror investigations that show benefit of a variety of vaccinations in AD [ 78 , 79 , 80 , 81 , 82 ].…”
Section: Bcg and Neurodegenerative Diseasesupporting
confidence: 71%
See 1 more Smart Citation
“…These studies mirror investigations that show benefit of a variety of vaccinations in AD [ 78 , 79 , 80 , 81 , 82 ].…”
Section: Bcg and Neurodegenerative Diseasesupporting
confidence: 71%
“…In a follow-up, multi-cohort study again it was shown that intravesicular BCG imparted a protective benefit against risk of AD; interestingly, it also showed protection against Parkinson’s disease [ 72 ]. A recent open-label, non-placebo-controlled study employing BCG in cognitively normal participants showed a reduction of AD risk as measured by plasma amyloid [ 78 ].…”
Section: Bcg and Neurodegenerative Diseasementioning
confidence: 99%
“…In those who completed 9 months following vaccination, their APS scores revealed a reduction in all the risk groups, but of different statistical significances: low-risk group ( p = 0.37), intermediate-risk group ( p = 0.13), and the high-risk group (statistically significant, p = 0.016). Greater benefit was seen in younger participants and those with the highest risk [ 56 ].…”
Section: Protective Effects Of Bcg Against Dementiamentioning
confidence: 99%
“…Other herpetic vaccinations, for instance for shingles (varicella-zoster) have been associated with a 15% reduced risk of AD and other neurodegenerative diseases ( Lehrer and Rheinstein, 2022 ). A prospective study (albeit proof of concept with n = 49) with the Bacillus Calmette–Guérin (BCG) vaccine for tuberculosis has also provided positive data that will stimulate additional interest in the role of vaccines as a protection against AD ( Dow et al, 2022 ). Whether benefits are seen with COVID-19 vaccinations remains to be analysed.…”
Section: Hypotheses and Drug Targetsmentioning
confidence: 99%